ANALISIS KELAYAKAN FINANSIAL PROYEK JALAN TOL SISTEM KONSESI SINGLE PERIOD MELALUI PENDEKATAN STOKASTIK - M Sarpan (Fakultas Teknik Universitas Pasir Pengaraian, 2020)
Pekanbaru-Dumai Toll Road Section-1 includes the acceleration of Sumatra toll road development, this study conducted a financial feasibility analysis on the investment with a single period concession an analysis of the stochastic approach with the using of software -at-risk version 7.6.1 also with deterministic approach as a comparison, Section 1 of the Pekanbaru-Dumai toll road investment amount Rp. 1,766,858,970,000 with an equity proportion of Rp. 1,236,808,000,000 and debt of Rp. 530,050,970,000. The results of NPV calculations using the deteriministic approach at low risk Rp. 100,247.04 million, moderate risk Rp. 99,492.09 million, high risk Rp. 97,280.99 million, and with a stochastic approach to low risk Rp. 574,617.27 million, medium risk Rp. 544,400.74 million, high risk Rp. 512,530.56 million. Based on the analysis results, the Pekanbaru-Dumai toll road section-1 project is financially feasible.